2015
DOI: 10.1007/s10902-015-9686-9
|View full text |Cite
|
Sign up to set email alerts
|

Affect and Affect Regulation Strategies Reciprocally Influence Each Other in Daily Life: The Case of Positive Reappraisal, Problem-Focused Coping, Appreciation and Rumination

Abstract: International audienceFeelings of positive or negative affect are not restricted to temporary states. They can also determine future affective experiences, by influencing the building of an individual’s personal resources. The present study was designed to understand the daily fluctuations in positive and negative affect more fully. To this end, we examined the involvement of a variety of affect regulation strategies in these fluctuations. The affect regulation strategies we explored included positive reapprai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 49 publications
6
54
1
2
Order By: Relevance
“…The idea that affective feelings can influence the implementation of affect regulation strategies is also supported by some theories pertaining to the broad impact of affective experience on cognition and behaviour (Bowers, 1991;Fredrickson, 1998Fredrickson, , 2001 and has been confirmed by empirical studies (Burns et al, 2008;Fredrickson & Joiner, 2002;Moberly & Watkins, 2008;Pavani, Le Vigouroux, Kop, Congard, & Dauvier, 2015). Contrary to what recent models of affect regulation state (Gross, 2015;Kuppens, Oravecz, et al, 2010b), these theories and findings suggest that there are at least as many positive feedback loops between affect and affect regulation strategies as there are negative ones.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The idea that affective feelings can influence the implementation of affect regulation strategies is also supported by some theories pertaining to the broad impact of affective experience on cognition and behaviour (Bowers, 1991;Fredrickson, 1998Fredrickson, , 2001 and has been confirmed by empirical studies (Burns et al, 2008;Fredrickson & Joiner, 2002;Moberly & Watkins, 2008;Pavani, Le Vigouroux, Kop, Congard, & Dauvier, 2015). Contrary to what recent models of affect regulation state (Gross, 2015;Kuppens, Oravecz, et al, 2010b), these theories and findings suggest that there are at least as many positive feedback loops between affect and affect regulation strategies as there are negative ones.…”
Section: Introductionmentioning
confidence: 88%
“…Gross, 2015;Kuppens, Oravecz, et al, 2010b), theories on the broad impact of affective experiences on cognition and behaviour (i.e. Bowers, 1991;Fredrickson, 1998Fredrickson, , 2001, and several initial studies (Burns et al, 2008;Fredrickson & Joiner, 2002;Moberly & Watkins, 2008;Pavani et al, 2015), all agree that reciprocal influences can exist between affect and affect regulation strategies. Given that these influences operate over time (affective experiences determine the subsequent implementation of affect regulation strategies which, in turn, determines fresh affective feelings), they presumably constitute the dynamics of affect regulation.…”
Section: Introductionmentioning
confidence: 96%
“…For instance, when experimentally induced in daily life, rumination predicts an increase in concurrent NA levels (Huffziger et al, 2012). Further, uninstructed ruminative response deployment has been linked to reduced positive affect and increased NA across EMA observations (Brans et al, 2013;Pavani, Le Vigouroux, Kop, Congard, & Dauvier, 2016), and a delayed return to baseline levels (Pavani et al, 2016). Others have also demonstrated that ruminative self-focus exacerbates depressive affect over time among symptomatic college students (Connolly & Alloy, 2017), and among adults with mood and anxiety disorders, for whom rumination after daily stressors increased NA and decreased positive affect (Ruscio et al, 2015).…”
Section: Rumination and Emotion Dysregulation In Daily Lifementioning
confidence: 99%
“…As a result, emotion-focused, rather than problem-focused, coping strategies are commonly used. Such emotionfocused coping strategies include minimizing, avoidance coping, appreciation, and positive reappraisal (Folkman & Lazarus, 1988;Pavani, Le Vigouroux, Kop, Congard, & Dauvier, 2016). Unlike denial, which represses the existence of a risk, minimizing is a coping mechanism in which one refuses to ruminate on a risk while continuing on in a stoic manner, as if there was little threat at all (Aldwin & Revenson, 1987).…”
Section: Coping Mechanismsmentioning
confidence: 99%
“…In a similar vein avoidance, while doing little to change the stressor like problem-focused coping does, could be useful in such situations where interpersonal conflict may be risky and circumventing the stressor is the safest strategy (Riordan et al, 1991). Conversely, appreciation pertains to emphasizing and treasuring features of a situation or an environment that results in creating a meaningful link (Pavani et al, 2016), for instance, appreciating the magnificent glaciers of Alaska opposed to lamenting the cold, northerly wind. Supporting the idea that appreciation is an important coping mechanism in fishermen, previous research found that fishermen are more optimistic than a comparison group of land-based employees (Riordan et al, 1991).…”
Section: Coping Mechanismsmentioning
confidence: 99%